The Effectiveness of Mindfulness Deep Breathing in Classical Format to Increase Students’ Academic Engagement (Jurnal Bimbingan Konseling, 2020)
Studies related to mindfulness deep breathing up to this point have been focused on individual and group contexts. Therefore, this study aimed to prove that mindfulness deep breathing in classical format is effective to increase students’ academic engagement. This study used multiple pretest posttest research design. Meanwhile, the subjects were students of X IPA 1 and IPA 3 classes in SMA Kesatrian 2 Semarang. To collect the data, this study used Student Engagement Instrument (SEI) which focused on affective and cognitive aspects. The results of repeated measure test proved that mindfulness deep breathing in classical format was effective to increase students’ academic engagement (F(1.72) = 315.05; p < 0.001). In addition, within subject test showed an increase in pre-test (M = 176.76; SD = 8,81), post-test (M = 113.76; SD = 8.57), and follow-up (M = 120.79; SD = 6.169). In brief, the mindfulness deep breathing implemented in the classroom effectively increased students’ academic engagement.